(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess sleep quality, the demand for traditional medicine treatment for sleep disorders, and to identify factors related to sleep quality in patients with hypertension. Subject and methods: A cross-sectional descriptive study was conducted on 200 hypertensive patients at health stations in Ngu Dien Commune, Phong Dien District, Thua Thien Hue Province, using the Pittsburgh Sleep Quality Index (PSQI). Results: The average PSQI score was 9.07 ± 4.21, and 67 % of patients expressed a demand for traditional medicine treatment for sleep disorders. Among them, the demand for traditional medicine-based medication was the highest, accounting for 41.6%. Conclusion: The majority of patients had poor sleep quality. Age, education level, occupation, and the demand for traditional medicine treatment for sleep disorders were statistically significantly associated with patients’ sleep quality.